Mineralogy and Geochemistry of Copper Deposits in Samaenre Village, Tonra Sub-District, Bone District, South Sulawesi Province - Wakila, Muhamad Hardin; Heriansyah, Andi Fahdli; Rizky Nurul Aulia; Muhaimin, Al (Cognitia : International Engineering Journal, 2025)
Samaenre Village has supergene copper mineralisation in rocks of the Kalamiseng Formation and geographically adjacent to diorite intrusions. The mineralisation outcrops are associated with alteration that changes the volcanic rocks of the Kalamiseng Formation. Previously, research was conducted on the characteristics of hydrothermal alteration and its alteration type in the Tonra area of Bone Regency, South Sulawesi Province. However, the research did not specifically examine the types of copper ore minerals and their associations and did not determine the copper content at the research location. The purpose of this study was to determine the types of copper ore minerals, associated minerals and copper  content in samples in the study area. The analytical method used in this research is first carried out megaskopis analysis to determine the physical properties of the sample. After that, laboratory analyses of mineragraphy, X-Ray Diffraction (XRD) and Atomic Absorption Spectrophotometer (AAS) were carried out. The results of megascopic analysis of the two research samples have a fresh blue colour and a fresh green colour with a brown weathered colour, there are calcite minerals and also tend to oxidise. Copper ore minerals found based on Mineragraphy and XRD analysis are Cuprorhodsite (CuFeRh2S4), Auricuprite (Cu3Au), Tenorite (CuO), Cuprite (Cu2O). The associated minerals found based on the results of Mineragraphy and XRD analysis are Cupalite (Al5Cu5), Diopside (CaMgSi2O6), Siderite (FeCO3), and Diopside (CaMgSi206). The copper (Cu) content in samples from the study area based on AAS analysis results ranged from 0.11 % to 0.17 % Cu